RELATIONSHIP BETWEEN GROWTH RATE AND DIFFERENT TYPES OF INFECTION IN CHILDREN UNDER 5 YEARS ON WEST PAPUA - Pratomo, Fransiskus Aryo (Institute of Topical Disease Universitas Airlangga, 2017)
Malnutrition is still a significant problem in the world and in Indonesia. Among the factors underlying it, the role of growth faltering is often underestimated. Considering infection as a factor that affects growth and that Indonesia is endemic to various different infectious diseases, to understand its role, a study on infants is conducted using using longitudinal study design in the Sumuri District, Bintuni Bay Regency, West Papua Province. A total of 138 children aged 6 months to 5 years is followed for 6 months in February to August 2014. Weight gain data and frequency of infection is collected, with the infections divided into four category of disease: upper respiratory tract infection, skin infection, gastroenteritis, and malaria. These data are gathered by Puskesmas daily and monthly records followed by home visit. This study found that the prevalence of malnutrition for the area covered by Puskesmas Tanah Merah is 15.9% for moderate malnutrition and 2.9% for severe malnutrition, with the mean SD value in the beginning of the study -1.15 and at the end of study -1.12, with the difference of SD value calculated as weight gain. Total incidence of infections and mean duration of each infection is then compiled and calculated with weight gain data using linear regression method statistical test to understand the difference of role of each infection to weight gain. The result of the study shows that gastroenteritis has a significant negative effect to weight gain and upper respiratory tract infection has a negative effect to weight gain on children in the villages handled by Puskesmas Tanah Merah West Papua.